An experimental study of a novel integrated desiccant air conditioning system for building applications - Elmer, Theo; Worall, Mark; Wu, Shenyi; Riffat, Saffa (Elsevier, 2016)
To date, the application of liquid desiccant air conditioning systems in built environment applications, particularly small scale, has been limited. This is primarily due to large system size and complexity, issues of desiccant solution leakage and carry-over and equipment corrosion. As a result, a novel integrated desiccant air conditioning system (IDCS) has been developed. The system combines the regenerator, dehumidifier and evaporative inter-cooler into a single membrane based heat and mass exchanger. This paper presents an evaluation, based on experimental data, of the novel IDCS operating with a potassium formate (CHKO2) desiccant working fluid. A range of tests have been completed to characterise the performance of the dehumidifier, regenerator and complete IDCS. Cooling output in the range of 570 to 1362W and dehumidifier effectiveness in the range of 30 to 47% are presented. An issue encountered has been an imbalance between moisture removal rate in the dehumidifier and moisture addition rate in the regenerator. As a result, an adjusted thermal COP (COPth,adj) value has been calculated. COPth,adj values of 1.26 have been achieved with an average of 0.72. Electrical COP (COPel) values of 3.67 have been achieved with an average of 2.5.